Efficacy of Bedside Respiratory Muscle Training in Patients With Stroke: A Randomized Controlled Trial. (October 2018) - Yoo, Hyun-Joon; Pyun, Sung-Bom
Abstract : Objective: Inspiratory and expiratory muscles are important for effective respiratory function. This study aimed to investigate the efficacy of bedside respiratory muscle training on pulmonary function and stroke-related disabilities in stroke rehabilitation. Design: Patients with stroke ( N = 40) in a rehabilitation unit were randomly assigned to either the intervention group ( n 1 = 20) or the control group ( n 2 = 20). Both groups participated in a conventional stroke rehabilitation program. During the study period, the intervention group received bedside respiratory muscle training twice a day for 3 wks. The respiratory muscle training consisted of (1) a breath stacking exercise, (2) inspiratory muscle training, and (3) expiratory muscle training. The primary outcomes were measures of pulmonary function: forced vital capacity, forced expiratory volume in 1 sec, and peak flow. Secondary outcomes were stroke-related disabilities assessed using the National Institutes of Health Stroke Scale, Modified Barthel Index, Berg Balance Scale, Fugl-Meyer Assessment, the Korean Mini-Mental State Examination, and pneumonia incidence. Results: Pulmonary function was significantly improved in the intervention group after 3 wks of respiratory muscle training ( P < 0.05). This improvement in pulmonary function was independent of the improvement in stroke-related disabilities. Conclusion: Three weeks of respiratory muscle training had significant effects on pulmonary function in stroke survivors. To Claim CME Credits: Complete the self-assessment activity and evaluation online athttp://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to: (1) Appreciate the respiratory function changes that occur in patients following a stroke; (2) Describe appropriate inspiratory and expiratory muscle training techniques to improve pulmonary function in patients following a stroke; (3) Enhance ability to implement inpatient; and (4) Determine appropriate respiratory training programs for patients following stroke. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity. Abstract : Supplemental digital content is available in the text.